A Ciência Aberta e os desafios do intérprete de libras na esfera jurídica: do cadastramento à mediação dos discursos na sala de audiência - Ramos, Luana Manini Genari de Souza (2023)
Open science represents a new approach in the scientific process that values open access to research data and promotes the sharing of information, facilitating the reuse of data by researchers and society in general. This movement allows data to be accessible and available, promoting transparency, collaboration, and the possibility of new interpretations of studies, driving development and scientific advances for society as a whole. This research, with the support of CNPq, is inserted in the Open Science and, more specifically, in the Multimodal/Multilingual Portal, allowing the circulation of knowledge beyond the walls of the academy, promoting, in a transparent and accessible way, the monitoring of the course of research that, although it is a consolidated practice in other areas of knowledge, such as natural and exact sciences, in the humanities it is recent. The goal of this research is to understand the challenges that sign language interpreters (SIs) face in the legal sphere, from the registration as Auxiliaries of Justice to the mediation of discourses between deaf people signers of Brazilian Sign Language — Libras with other non-deaf people who speak the Portuguese language, in the interpretative act of the hearing genre. Given the complexity of the different audiences and the specificity of the interpretation processes involving sign languages and oral languages, this research will play an important role in understanding this specific discursive interaction, considering that the interpreter of Libras is equated to an expert with a high degree of complexity and responsibility in the service he performs. The corpus was composed of concrete statements from the questionnaire prepared by Google Forms and interviews conducted remotely by audiovisual recording system, via the Teams tool with the professional Pounds Interpreters who have already been appointed and are included in the Public Consultation of the management system of the Auxiliaries of Justice of the Court of Justice of the State of São Paulo. In the analysis of the statements in dialogue, we tried to identify the challenges faced by each professional to act in communicative interaction in the courtroom. The purpose is to propose, as complementary training based on legal literacy a systematized protocol that will serve to understand the steps from registration to act as interpreter of Libras in Common Justice. The basic foundation will be the Dialogical Discourse Analysis, associated with other areas of knowledge, such as Law and Translation and Interpretation Studies, considering the demand of interpreters in the legal context in search of an interdisciplinary training